2015
DOI: 10.1063/1.4922141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen partial pressure on the microstructural and magnetic properties of Er-doped ZnO thin films

Abstract: Er-doped ZnO thin films have been prepared by using inductively coupled plasma enhanced physical vapor deposition at different O2:Ar gas flow ratio (R = 0:30, 1:30, 1:15, 1:10 and 1:6). The influence of oxygen partial pressure on the structural, optical and magnetic properties was studied. It is found that an appropriate oxygen partial pressure (R=1:10) can produce the best crystalline quality with a maximum grain size. The internal strain, estimated by fitting the X-ray diffraction peaks, varied with oxygen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…Also, a diamagnetic and paramagnetic contribution appear in the hysteresis loop of pure ZnO sample at about 0.8 Tesla as M decreases with the increasing of H. This indicates the surface and ligand induced defects [39].The samples with x = 0.01 exhibits a room temperature ferromagnetism which may be caused by the substitution of Er 3+ in Zn 2+ sites rather due to the formation of any ferromagnetic secondary phase. Similar results were obtained by Chen et al [40] for Er-doped ZnO thin films prepared by coupled plasma enhanced physical vapor deposition. They reported that because the Er 2 O 3 powder has a paramagnetic property, it is logical to consider that the observed room temperature ferromagnetism is the intrinsic property of Er-doped ZnO films, and the ferromagnetism is a result of the substitution of Er 3+ in Zn 2+ sites.…”
Section: Magnetic Measurementssupporting
confidence: 89%
“…Also, a diamagnetic and paramagnetic contribution appear in the hysteresis loop of pure ZnO sample at about 0.8 Tesla as M decreases with the increasing of H. This indicates the surface and ligand induced defects [39].The samples with x = 0.01 exhibits a room temperature ferromagnetism which may be caused by the substitution of Er 3+ in Zn 2+ sites rather due to the formation of any ferromagnetic secondary phase. Similar results were obtained by Chen et al [40] for Er-doped ZnO thin films prepared by coupled plasma enhanced physical vapor deposition. They reported that because the Er 2 O 3 powder has a paramagnetic property, it is logical to consider that the observed room temperature ferromagnetism is the intrinsic property of Er-doped ZnO films, and the ferromagnetism is a result of the substitution of Er 3+ in Zn 2+ sites.…”
Section: Magnetic Measurementssupporting
confidence: 89%